PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VI SD NEGERI 007 PENDALIAN KECAMATAN PENDALIAN IV KOTO KABUPATEN ROKAN HULU - Mohammad Taofik Saifullah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
This research is motivated by the low learning outcomes of students in the SD Negeri 007 Pendalian KecamatanPendalian IV Koto Kabupaten Rokan Hulu. This study aims to improve the learning outcomes of IPS students ofclass VI SD Negeri 007 Pendalian Kecamatan Pendalian IV Koto Kabupaten Rokan Hulu with theimplementation of cooperative learning model type numbered heads together, which is held for 1 month. Thesubjects of this study are the students of class VI SD Negeri 007 Pendalian Kecamatan Pendalian IV KotoKabupaten Rokan Hulu which amounted to 40 people academic year 2016-2017. The form of research isclassroom action research. The instrument of this research consisted of performance instrument and datacollection instrument in the form of observation sheet of teacher activity and student activity. Based on theresults of research that has been done, it is known that cooperative learning model type numbered headstogether can improve the results of IPS student grade VI SD Negeri 007 Pendalian Kecamatan Pendalian IVKoto Kabupaten Rokan Hulu. This is evident from the repetition of cycle I the average score of studentsincreased 12.1% points from the basic score of students to 76.6%. In cycle II increased 4.8% points from cycle Ito 81.4%. From the data can be interpreted that the implementation of cooperative learning model typenumbered heads together can improve the learning outcomes of IPS students class VI SD Negeri 007 PendalianKecamatan Pendalian IV Koto Kabupaten Rokan Hulu.